Optimalisasi Pengetahuan Siswa-Siswi SMK Bhina Karya Karanganyar Dengan Penyuluhan Mengenai Penyakit Mental (Mental Illness) - Liss Dyah Dewi Arini; Erma Nurhayati Firdaus; Saryadi Saryadi; Musta’in Musta’in; Aditya Kurniawan (jurnal ABDIMAS Indonesia, 2024)
Knowledge about mental illness for Bhnike Karya Karanganyar Vocational School students is still limited. Knowledge about waste disposal management is important to provide as an effort to equip oneself to maintain personal health (Radiani, 2019). If mental disorders are not treated properly, they will get worse and can ultimately burden families, society and the government. The method used in this paper is exploratory descriptive analysis, through literature reviews and secondary data studies. The research results show that a study of the 2018 Riskesdas data shows that the prevalence of serious mental disorders in the Indonesian population is 7% (per mile of population) and is mostly found in Bali, Yogyakarta, NTB and Aceh. It is hoped that similar activities can have an impact on increasing awareness of the Indonesian people, especially students and female students as the younger generation, to actively participate in maintaining mental health. On this occasion, the Community Service Implementer of the D3 Medical Records and Health Information Study Program, Faculty of Health Sciences, Duta Bangsa University, Surakarta will carry out P2M activities for Bhina ​​Karya Karanganyar Vocational School students regarding mental illness. On this occasion, the Community Service implementer expressed his thanks to the Head of the School and the Head of Public Relations at Bhina ​​Karya Karanganyar Vocational School for providing permission for a place to carry out Community Service activities. Hopefully this activity will be useful for increasing the knowledge of Bhina ​​Karya Karanganyar Vocational School students regarding mental illness in the hope that their knowledge will be aware of maintaining mental conditions for the sake of mental health itself.